Gregory rabassa’s views on translation (2011)
Gregory Rabassa is noted for his translations of famous Latin American authors (García Márquez, Vargas Llosa, Clarice Lispector, Jorge Amado, etc.). Less known are his views on translating. In this paper I aim at presenting and discussing his viewpoints as to the definition of translation (with a key discussion of the concept of equivalence), the role of the translator (a model speaker-listener of the target text), and some of the translation strategies he applies in his translational work (original's pre-eminence, problem solving, foreignizing, fictionalizing, and semantic networking). I argue that most of Rabassa's stances towards translating can be explained and are still valid within the framework of a modern translation approach. Examples from the English, French, German, Portuguese and Russian translations of García Márquez's Cien años de soledad are taken from a multilingual parallel corpus collected by the author of this paper.